Do comportamento político à psicologia política no Brasil: a história da psicologia política vista pelos participantes da Associação Brasileira de Psicologia Política - Veiga, Maria Aparecida Cunha Malagrino (2017)
The main objective of this study is to present the trajectory of Political Psychology in Brazil seen from its precursors and other participants. These characters were divided into three generations of researchers considering the degree of academic relationship. The main sources of data for this study were documentary research, interviews and genogram built from data from the Lattes Platform. As an investigative procedure we work from the oral history of the subject with which we could combine the written sources of the documentary set (minutes, notebooks, journals, annals) with oral sources (interviews). The results of the research show how the researchers of the three generations examined consider the development of Political Psychology in Brazil over a period of 16 years